আবদুশ শাকুরের শ্রেষ্ঠ প্রবন্ধ - শাকুর, আবদুশ (ঢাকা : রোদেলা প্রকাশনী, 2011)
Selected critical essays chiefly on Bengali literature.
Donated By Akbar Ali Khan
In Bengali.
Keywords: Bengali literature -- History and criticism; Bengali essays